Proteotoxic stress response in atherosclerotic cardiovascular disease: Emerging role of heat shock factor 1 - Ghai, Shruti; Young, Alex; Su, Kuo-Hui (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis is a major risk factor for cardiovascular diseases. Hypercholesterolemia has been both clinically and experimentally linked to cardiovascular disease and is involved in the initiation of atherosclerosis. Heat shock factor 1 (HSF1) is involved in the control of atherosclerosis. HSF1 is a critical transcriptional factor of the proteotoxic stress response that regulates the production of heat shock proteins (HSPs) and other important activities such as lipid metabolism. Recently, HSF1 is reported to directly interact with and inhibit AMP-activated protein kinase (AMPK) to promote lipogenesis and cholesterol synthesis. This review highlights roles of HSF1 and HSPs in critical metabolic pathways of atherosclerosis, including lipogenesis and proteome homeostasis.